Hoaks Di Era Media Sosial Dalam Perspektif Al-Quran - Balqis Qonita; Abdul Fatah (CV. ITTC INDONESIA, 2025)
This study aims to explore the Qur'an's perspective on the phenomenon of hoaxes in the era of social media and to provide guidelines for Muslims in responding to the increasingly widespread dissemination of false information. This study uses a library research method with a descriptive qualitative approach. Data was collected through a review of relevant literature, including Qur'anic exegesis, books on Islamic communication ethics, articles related to hoaxes and social media, and previous research findings. Data analysis was conducted using a qualitative analysis model consisting of three stages: data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the Qur'an provides clear guidance on the importance of verifying information and avoiding the spread of false news. Surah Al-Hujurat verse 6 teaches the principle of tabayyun (clarification) as an important step in verifying the information received. This study also reveals that hoaxes in the context of social media can cause social unrest and worsen interfaith harmony. The Qur'an reminds Muslims not to blindly follow or spread information whose truthfulness is unclear, as explained in Surah Al-Isra' verse 36 and Surah An-Nur verse 11. Based on these findings, the values contained in the Qur'an, such as the obligation to verify news and maintain social dignity, can serve as guidelines to counter the spread of hoaxes in the digital age. This study concludes that the teachings of the Qur'an are highly relevant to be applied in social life in the era of social media, to create a more wise and responsible society in disseminating information.